Advances in planar lipid bilayers and liposomes. - Iglic, Ales (Elsevier, Academic Press, 2015)
The Elsevier book-series Advances in Planar Lipid Bilayers and Liposomes, provides a global platform for a broad community of experimental and theoretical researchers studying cell membranes, lipid model membranes and lipid self-assemblies from the micro- to the nanoscale. Planar lipid bilayers are widely studied due to their ubiquity in nature and find their application in the formulation of biomimetic model membranes and in the design of artificial dispersion of liposomes. Moreover, lipids self-assemble into a wide range of other structures including micelles and the liquid crystalline hexagonal and cubic phases. Consensus has been reached that curved membrane phases do play an important role in nature as well, especially in dynamic processes such as vesicles fusion and cell communication. Self-assembled lipid structures have enormous potential as dynamic materials ranging from artificial lipid membranes to cell membranes, from biosensing to controlled drug delivery, from pharmaceutical formulations to novel food products to mention a few. An assortment of chapters in APLBL represents both an original research as well as comprehensives reviews written by world leading experts and young researchers.